STRATEGI ALOKASI ANGGARAN SEKTOR PERTANIAN UNTUK MEMPERCEPAT PEMBANGUNAN DAERAH DI KABUPATEN PANDEGLANG PROVINSI BANTEN - Wahyuni, Eling Sri; Firdaus, Muhammad; Baga, Lukman M Mohammad (Jurnal Manajemen Pembangunan Daerah, 2018)
The agricultural sector is one of the leading sectors in Pandeglang Regency. This study aims to describe the process of preparing and implementing agricultural sector budgets, analyzing the effect of agricultural sector and labor of the agricultural sector expenditure toward the growth of the agricultural sector regionally in Banten Province, and then formulating appropriate strategies in budget allocation and agricultural sector development. This study uses secondary data and primary data with descriptive analysis tools, regression analysis using panel data, and SWOT analysis. The results showed that the agricultural sector has become a priority in various planning documents in Pandeglang District including RPJP, RPJMD, and RKPD Pandeglang District. Then from the result of regression analysis using panel data, it is resulted that government expenditure for agriculture sector have positive and significant effect toward PDRB of agriculture sector. Meanwhile, the labor of agricultural sector has negative and significant effect toward GDP of agriculture sector. From the results of objectives 1 and 2 and supported by primary data through in-depth interviews could be formulated 10 strategies of budget allocation and development of agricultural sector in Pandeglang Regency.Keywords: Strategy, Agricultural Sector, Budget